2015
DOI: 10.1186/s13075-015-0539-z
|View full text |Cite
|
Sign up to set email alerts
|

IgG anti-apolipoprotein A-1 antibodies in patients with systemic lupus erythematosus are associated with disease activity and corticosteroid therapy: an observational study

Abstract: IntroductionIgG anti-apolipoprotein A-1 (IgG anti-apoA-1) antibodies are present in patients with systemic lupus erythematosus (SLE) and may link inflammatory disease activity and the increased risk of developing atherosclerosis and cardiovascular disease (CVD) in these patients. We carried out a rigorous analysis of the associations between IgG anti-apoA-1 levels and disease activity, drug therapy, serology, damage, mortality and CVD events in a large British SLE cohort.MethodsSerum IgG anti-apoA-1 levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In addition, sample size may play a role since this is the first large-scale study of anti-apoA-1 IgG in the community. Furthermore, as only baseline anti-apoA-1 IgG levels were measured, we could not assess potential variations of anti-ApoA-1 IgG levels over time (38) and especially after cardiovascular events, a point that will need to be determined in future studies.…”
Section: Prevalence Of Anti-apoa-1 Igg In the General Populationmentioning
confidence: 99%
“…In addition, sample size may play a role since this is the first large-scale study of anti-apoA-1 IgG in the community. Furthermore, as only baseline anti-apoA-1 IgG levels were measured, we could not assess potential variations of anti-ApoA-1 IgG levels over time (38) and especially after cardiovascular events, a point that will need to be determined in future studies.…”
Section: Prevalence Of Anti-apoa-1 Igg In the General Populationmentioning
confidence: 99%
“…Among other autoantibodies of possible cardiovascular relevance, we and others focused our interest on antibodies to apolipoprotein A-1 (apoA-1), the major protein fraction of high-density lipoprotein (HDL). High levels of anti-apoA-1 IgG have been initially described in patients with prothrombotic autoimmune diseases associated with an increased CV risk such as systemic lupus erythematosus (13)(14)(15), and primary anti-phospholipid syndrome (16). Later on, these autoantibodies were found to be elevated in high CV risk settings, such as acute coronary syndromes (17)(18)(19)(20), severe carotid stenosis (21,22), end-stage renal disease (23), and rheumatoid arthritis patients (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently proposed that apo‐A1 prevents autoimmunity and suppresses inflammation independently of cholesterol transport . Indeed, several studies showed that the levels of anti‐apo‐A1 and anti‐HDL antibodies were significantly higher in patients with systemic lupus erythematosus (SLE) and other systemic autoimmune disorders, and were positively associated with disease activity. Thus, another possible explanation for current results is that lower HDL‐C may represent more severe underlying disease and consequently a higher risk of osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%